Identifikasi Pola Redistribusi Tanah Untuk Pendugaan Erosi Berdasarkan Nilai Suseptibilitas Magnetik di Daerah Bukit Nobita Kota Padang - Fadillah, Ahmad; Budiman, Arif (Jurnal Fisika Unand, 2023)
Research has been carried out to identify soil redistribution patterns of soil redistribution as an estimate of erosion by analyzing the magnetic susceptibility values of soil samples in the Bukit Nobita area, Padang City. Soil samples were taken from two different areas, namely areas that are not vegetated and areas that are vegetated. The length of the track to each area is 100 m consisting of 10 points with variations in depth at each point, namely 10, 20, 30, 40, and 50 cm. The magnetic susceptibility measurement of the sample uses a Magnetic Susceptibility Meter with the commonly used frequencies, namely Low Frequency (LF) and High Frequency (HF). The measurement results show that for non-vegetatedareas, the χlfvalues range from 44 10-8 m3kg-1 to 301 10-8 m3kg-1, and theχhfvalue ranges from 43 10-8 m3kg-1 to 298.9 10-8 m3kg-1. Whereas for samples from vegetated areas, the χlf values range from 63.6 10-8 m3kg-1 to 859.410-8 m3kg-1, and the χhf ranges from 63.1 10-8 m3kg-1 to 852,5 10-8 m3kg-1. The results showed that the susceptibility value depends on the frequency (χfd), which is <2% and was dominated by large magnetic minerals that were disturbed, such as erosion. The distribution profile of χlf values tends to increase with increasing sampling depth, indicating that the soil in both tracks is disturbed, and the redistribution pattern of soil in non-vegetated areas is more evenly distributed than vegetated areas, allowing erosion to also occur in vegetated areas.